The chemokines CCL22 and CCL17 are a defining feature of type 2 stimulated human lung macrophages and exhibit different metabolic dependencies - Ridley, Amanda J. L.; Curle, Annabel J.; Colombo, Stefano A. P.; Hughes, Joshua J.; Dyer, Douglas P.; Simpson, Angela; Booty, Lee M.; Feeney, Maria; Cook, Peter C.; MacDonald, Andrew S. (Frontiers in Immunology, 2025)
IntroductionAlthough human lung macrophages are heterogenous and play key roles during health and disease, the mechanisms that govern their activation and function are unclear, particularly in type 2 settings. Our understanding of how human lung macrophages respond to inflammatory signals have predominantly relied on cell lines or peripheral blood derived cells, which have a limited capacity to reflect the complexity of tissue macrophage responses.MethodsWe isolated macrophages from resected human lung tissue and stimulated them ex vivo under type 2 (IL-4, IL-13, or IL-4 + IL-13) or type 1 (IFNγ + LPS) conditions.ResultsHuman lung macrophages stimulated with IL-4/13, alone or in combination, significantly upregulated expression of the chemokines CCL17, CCL18 and CCL22, along with the transglutaminase TGM2 and the lipoxygenase ALOX15. This type 2 activation profile was distinct from LPS + IFNγ activated human lung macrophages, which upregulated IL6, IL8, IL1B, TNFα and CHI3L1 (YKL-40). Further, type 2 activated human lung macrophage products showed differential metabolic reliance for their induction, with IL-4/13 induced CCL22 being glycolytically controlled, while ALOX15 was regulated by fatty acid oxidation.DiscussionThese data clarify hallmarks of human lung macrophage activation and polarisation in addition to revealing novel metabolic regulation of type 2 markers.